Examining the role of word of mouth in purchase decision: an insight from fashion store - Wiratama, Bayu; Wijaya, Angga Pandu; Prihandono, Dorojatun; Wijayanto, Andhi; Suhud, Usep (Business: Theory and Practice, 2022)
The fashion business has a dynamic that adapts to the trends that are lighthearted and favored. A store can survive by providing clothes that fit the trend and adapt to the wishes of consumers. Word of mouth has not been investigated much in providing information to consumers that a store is following the trend. The study aims to examine the role of word of mouth in mediating the effects of store atmosphere and brand loyalty toward purchase decisions. The research employs a quantitative approach, with 118 respondents appropriate as the research sample. The results indicate that brand loyalty, brand image, and word of mouth directly affect purchase decisions; however, store atmosphere does not affect consumer purchase. The result also indicates that word of mouth mediates brand loyalty, brand image, and store atmosphere towards consumer purchase decisions. Based on the result, word of mouth is a prominent aspect of determining purchase decisions. Consumers decide to purchase based on information suitable to the fashion trend. Positive information leads consumers to purchase; hence, the store should emphasize and utilize word of mouth to create consumer purchase decisions.